Implementasi Undang-Undang Nomor 15 Tahun 2001 Terhadap Penjualan Sepatu KW/Imitasi di Kota Gorontalo - Noerhadi Priyatna; Dian Ekawaty Ismail; Taufik Zulfikar Sarson (Pusat Riset dan Inovasi Nasional, 2024)
The sale or circulation of branded shoes without permission can take several forms, including the sale of KW PK (Perfect Kick) shoes, KW 1 shoes, factory denied shoes, shoes that do not pass quality control, etc., which occurs when branded shoes are traded. and sold without a license or permission from the company that owns the trademark or rights to the brand. This research discusses the legal prohibition on the circulation of KW shoes in Gorontalo City. This research uses empirical and normative legal research methods. The research aims to determine the causes of the circulation of KW shoes in Gorontalo City and the form of legal prohibition on the circulation of KW shoes. As a result of this research, researchers found that first, the widespread distribution of KW shoes in Gorontalo is generally caused by a number of factors as follows; 1). Economic factors and people's purchasing power; 2). The role of markets (trade) and supply of goods; 3). Public interest in well-known brands; 4). Consumerism culture and fashion trends in society; 5). Lack of consumer awareness of IPR; 6). Lack of supervision and law enforcement. Second, enforcement of the law on the distribution of KW shoes in Gorontalo City is caused by the following things; 1). Lack of supervision and monitoring from related parties; 2). Lack of public awareness of both traders and consumers regarding IPR.